Kewadatan Lesmana dalam Sastra Tulis dan Pertunjukan Wayang - Suprihana Suprihana; Udreka Udreka (Wayang Nusantara: Journal of Puppetry, 2020)
AbstractThis paper discusses the nature of Lesmana in the written text and the play text of the purwa leather puppet show. This paper also discusses the text's intertextual relationship, especially regarding the concept of the Lesmana wadat. The data used are Serat Rama Jasadipoera, Novel Anak Bajang Gushing Winds Sindhunata, and the play Banjaran Rahwono Ki Timbul Hadi Prayitno. Intertextual concepts are used as a theoretical framework. Methods of data analysis using qualitative descriptive methods. The finding of this study is that the concept of the Lesmana wadat in the three texts does not experience any deviation or change.AbstrakTulisan ini membahas kewadatan Lesmana dalam teks tulis dan teks lakon pertunjukan wayang  kulit purwa. Tulisan ini juga membahas hubungan intertekstual teks tersebut khususnya tentang konsep wadat Lesmana. Data yang digunakan ialah Serat Rama Jasadipoera, Novel Anak Bajang Menggiring Angin Sindhunata, dan lakon Banjaran Rahwono Ki Timbul Hadi Prayitno. Konsep intertekstual digunakan sebagai kerangka teori. Metode analisis data menggunakan metode deskriptif kualitatif. Temuan dari penelitian ini ialah konsep wadat Lesmana dalam ketiga teks tidak mengalami penyimpangan atau perubahan.